A Functional View of Hybrid-Cloud Environment: An Approach towards Use Cases and Best Practices - Prashant Tyagi; P. P. Sharada Devi (New Approaches in Engineering Research Vol. 9, 2021)
Hybrid-Cloud Environment is a promising area of research, considering the greater flexibility and agility that it provides to businesses for moving their workloads and applications onto the cloud environment, as business requirements and budgets fluctuate. Governments, nonprofits, educational institutions, Product and Service Oriented Companies are all leveraging a hybrid-cloud deployment model to modernize their Information Technology (IT) platform, improve service availability, expand IT capacity, build highly reliable, resilient fault tolerant applications, systems and infrastructure on cloud and innovate faster. This paper discusses best practices on how organizations can seamlessly integrate their on-premises infrastructure with cloud native solutions from various cloud vendors for extending and optimizing their hybrid-cloud environments. In response to the complexities involved in the hybrid-cloud deployment, the work in this paper also discusses some of the popular use cases and how organizations can leverage cloud analytics, artificial intelligence tools and scalability of their Hybrid-Cloud Environment whilst also maintaining greater control and operational flexibility over their data for compliance purposes.